Caught between the ethnic sides: Children growing up in a divided post-war community - Ajduković, Dean (Array, 2008)
The war-related process of disintegration of a highly integrated and multi-ethnic community is described using a series of studies done in the city of Vukovar (Croatia) as a case example. After analyzing the key points of the community social breakdown, the three roots of ongoing ethnic division are explored: the feelings of being betrayed by important others at life-important situations ; massive suffering and traumatization ; and lack of compassion and acknowledgment of the victimhood. These also influence the inner dynamic of the divided community in which the strong social norm is not to cross the ethnic lines in public. When the schools became divided after the war so that the Serb and Croat children started going to separate schools, opportunity to meet each other across the ethnic lines became and remained severely limited. The implications for children that grow up in an ethnically divided community are documented in a study of children’ s and parental inter-ethnic attitudes and behaviors. The study included 1, 671 students aged 12 to 16 and their parents. It showed that the children had more out-group biases and negative attitudes, and were more likely to choose discriminative behaviors towards their peers from the ether ethnic group. Consequences for the future community inter-ethnic relations in the post-war societies and life limitations the children face are discussed.